Laying performance, egg quality and hatchability traits of Japanese quail (coturnix coturnix japonica) fed a chromium yeast feed additive Layplus(R): Effect of Leptidinia reticulata on female quails (Bangladesh Journal of Animal Science, 2018)
A 12-week study was conducted at the Teaching and Research Farm of the Obafemi Awolowo University, Ile-Ife to evaluate the effect of dietary inclusion of LAYPLUS® (LP) on fertility and egg parameters of female Japanese quails, Coturnix coturnix japonica. Two hundred and ten birds of average weight of 167.75±3.94g were used for this study, and they were allocated randomly into seven treatment groups and replicated thrice. Group 1 served as control without inclusion of LAYPLUS®, while groups 2, 3, 4 and 5 had 250 mg/kg, 500 mg/kg, 750mg/kg and 1000mg/kg inclusion of LP and group 6 had 240mg/kg of vitamin E, respectively, and group 7 clomiphene citrate. Eggs were collected daily and egg production was calculated on a bird-day basis. The data obtained were analyzed using one-way ANOVA. There was significant increase (p